Computational assessment of the crystallization tendency of 1-ethyl-3-methylimidazolium ionic liquids - Červinka, Ctirad; Štejfa, Vojtěch (Physical chemistry chemical physics, 2021)
A test set of 20 1-ethyl-3-methylimidazolium ionic liquids, differing in their anions, is subjected to a computational study with an aim to interpret the experimental difficulties related to the preparation of crystalline phases of the selected species. Molecular dynamics simulations of the liquid phases, quantum-chemical symmetry-adapted perturbation theory calculations of the interaction energies within the ion pair, and density functional theory calculations of the cohesive energies of the crystal phases are used in this work to obtain the structural, energetic, and diffusion parameters of the materials. Correlations of fusion temperatures and enthalpies and temperatures of the glass transitions with 15 calculated parameters are investigated in order to interpret the trends of the phase behavior of the selected ionic liquids. Correlations of a fair significance are found between the glass transition temperatures and selected energetic, cohesive, and diffusion-related characteristics of the liquids; however, the correlations of calculated transport and some enthalpic properties are blurred by the limited accuracy of the non-polarizable CL&P force field for predicting these properties. 1-Ethyl-3-methylimidazolium acetate is found to have an exclusive position among those in the test set due to several outlying characteristics, such as the short contact distance of its counterions in the liquid, high pair interaction energies, and importance of the dispersion interactions for the collective cohesion, impeding its crystallization significantly.